Design options for high-speed OA-based fully differential buffers able to drive large loads. (August 2021) - Neag, Marius; Kovács, István; Oneț, Raul; Câmpanu, Iulian
Abstract: This paper presents several options for the design of OA-based highly linear fully differential voltage buffers able to drive heavy loads at frequencies in the tens of MHz range. The buffer is first implemented by using a telescopic OA with enlarged voltage swing; two circuits for controlling the common mode level of the output voltage are proposed. Next, two implementations based on the folded cascode transconductor with a Monticelli-type complementary source-followers second stage are presented. One of them uses complementary source followers embedded into the Monticelli gain stage, in order to lower the buffer output impedance. The proposed circuits have been implemented in a standard 0.35 μm CMOS technology as design options for a voltage buffer required by a downhole sensor used in geological surveys. There, they have to drive a standard one-OA difference amplifier which presents heavy, unbalanced loads to their positive and negative outputs, respectively 1.5 kΩ and 500Ω. Simulation results validate the designs, demonstrating that all four circuits meet the requirements: they handle sine voltages with amplitudes up to 2VPPDIFF at frequencies up to 100 MHz, with THD values better than 0.4% for signals in the tens of MHz range, achieving CMRR and PSRR values above 40 dB at 100 MHz, while consuming between 5.3 mA and 8.3 mA from a 3.3V supply.